Changing the Direction and Orientation of Electric Field During Electric Pulses Application Improves Plasmid Gene Transfer in vitro - Pavlin, Mojca (MyJove Corporation, 2011)
Gene electrotransfer is a physical method used to deliver genes into the cells by application of short and intense electric pulses, which cause destabilization of cell membrane, making it permeable to small molecules and allows transfer of large molecules such as DNA. It represents an alternative to viral vectors, due to its safety, efficacy and ease of application. For gene electrotransfer different electric pulse protocols are used in order to achieve maximum gene transfection, one of them is changing the electric field direction and orientation during the pulse delivery. Changing electric field direction and orientation increase the membrane area competent for DNA entry into the cell. In this video, we demonstrate the difference in gene electrotransfer efficacy when all pulses are delivered in the same direction and when pulses are delivered by changing alternatively the electric field direction and orientation. For this purpose tip with integrated electrodes and high-voltage prototype generator, which allows changing of electric field in different directions during electric pulse application, were used. Gene electrotransfer efficacy is determined 24h after pulse application as the number of cells expressing green fluorescent protein divided with the number of all cells. The results show that gene transfection is increased when the electric field orientation during electric pulse delivery is changed.